Experimental analysis of refrigeration system using phase change material for energy efficiency improvement - Kurtboğan, Dilara (My University, 2020)
Bu çalışmada bir soğuk oda içersine yerleştirilmiş faz değiştiren malzemelerin (FDM)seçimi yapılıp, FDM eklenmesinin kabin içi hava sıcaklıklarının değişimine, kompressordur-kalklarına, enerji verimliliğine, güç kesintisi sırasındaki sıcaklık korunumuna olanetkileri incelenmiştir. Deneyler için sentezlenmiş ve kapsüllenmiş FDM’lerin seçimigeniş bir literatür taraması ve titiz laboratuvar testleriyle yapılmıştır. FDM kapsülleri testedilmek üzere içi içe iki odadan oluşturulmuş bir klimatik oda test düzeneği içineyerleştirilerek farklı çalışma şartlarında kabin içi sıcaklık değişimi, kompressör dur-kalksüreleri üzerine olan etkileri incelenmiştir. Ayrıca, iç ve dış ortam sıcaklıklarıkoşullandırılarak yapılan testler sonucunda, ideal çalışma şartlarına göre oluşturulmuşdatalarla karşılaştırıldığında soğuk oda içerisine FDM eklemenin soğutma sistemininperformans katsayısını etkisi incelenmiştir. Farklı çalışma şartlarını incelemek amacıyladış ortam koşulları 30 °C, 20 °C ve 10°C olarak şartlandırılmıştır. Ayrıca kompresörünçalışma aralağı ayarlanarak kabin içi sıcaklığının belirlenen set değrerinden 2 °C, 4 °C ve6 °C sıcaklık farkları için kompresör çalışma verileri ve iç hava sıcaklık değişim grafiklerielde edilmiştir. Çoğu senaryoda FDM eklenmesi ile compressor dur-kalk sayısınıazaltarak compressor ömrünü uzatmaya katkı sağladığı gözlenmiştir. FDM’leridondurmak için gerekli elektrik gücü de performans hesapları için hesaplanmıştır. FDMlerin sisteme katkısı hesaplanırken soğutma sistemi tarfından harcanan gücün telafi süreside gözönüne alınmaktadır. Yapılan çalışmalara ek olarak güç kesintisi durumunda odasıcaklığının FDM’nin gizli ısısı sayesinde ne kadar süre korunduğu ve oda sıcaklığınındeğişimi de incelenmiştir.

This study presents selection of the phase change materials (PCMs) placed inside of acold storage room, and the effect of the addition of PCMs to the change in air temperatureinside the room, the compressor on-off periods, the energy efficiency, temperaturechange during a power failure. The selection of the PCMs, which are synthesized andencapsulated for the experiments, is also done by a broad literature search and meticulouslaboratory tests. In order to test them, PCM capsules were placed in a climatic room testrig formed by two chambers, and under different operating conditions their effects on thetemperature change in the cabin and stop-start times of the compressor were examined.Moreover, according to the experimental results which are conducted in conditioned innerand outer zones, outcomes of adding PCMs to a cold room to the COP of the refrigerationsystem while comparing to the compressor ideal working data are analysed. To observedifferent operating conditions the outer zone is set 30 °C, 20 °C and 10°C, and also byadjusting the working range of the compressor, compressor operation data and indoor airtemperature change graphs were obtained for the 2 °C, 4 °C and 6 °C temperaturedifferences from the determined set value of the cabin. In most of the scenarios, it isobserved that addition of the PCM reduces the number of compressor on-offs, whichhelps the compressor lifespan increase. The charge power required to freeze PCMs is alsocalculated for performance calculations. When calculating the contribution of PCMs tothe system, the compensation time of the power consumed by the cooling system is alsocalculated. In addition to the studies conducted, in the case of power failure how long theroom temperature is maintained due to the latent heat of the PCM and the change of theroom temperature are also examined.
Keywords: FAZ DEĞİŞTİREN MALZEMEFDM SOĞUTMASOĞUK DEPOLAMA PHASE CHANGE MATERIALPCMREFRIGERATIONCOLD STORAGETHERMAL ENERGY STORAGETES; Makine mühendisliği; Mechanical engineering